Establishment of loop-mediated isothermal amplification for Brucella detection using a warmer pad as a heating source - Yin-Bo, Ye (BioTechniques, 2022)
The study sought to establish a sensitive and specific on-site loop-mediated isothermal amplification (LAMP) for Brucella heated using a warmer pad. LAMP primers specific to the conserved BvrR gene were designed, and the LAMP reaction was optimized. The heating characteristics of the warmer pad were investigated. The detection validity (specificity, sensitivity) of clinical samples by warmer-pad LAMP (WP-LAMP) was compared with that of qPCR. The WP-LAMP method displayed high specificity and sensitivity for five Brucella gene copies. The detection of 104 clinical samples was 97.1% concordant with quantitative polymerase chain reaction. The results showed the success of the WP-LAMP for on-site detection. The method requires no special equipment and is conducive to the prevention and control of brucellosis